1998
DOI: 10.1002/(sici)1099-1085(19980615)12:7<1111::aid-hyp633>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry of shallow groundwater in an upland Scottish catchment

Abstract: Abstract:The hydrogeochemistry of shallow groundwater has been characterized in the Allt a' Mharcaidh catchment in the Scottish Cairngorms in order to: (i) assess the spatial and temporal variation in groundwater chemistry; (ii) identify the hydrogeochemical processes regulating its evolution; and (iii) examine the in¯uence of groundwater on the quality and quantity of stream¯ow. Shallow groundwater in super®cial drift deposits is circumneutral (pH $ 7 . 1) and base cation concentrations are enriched compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 31 publications
7
71
1
1
Order By: Relevance
“…Mean annual run-off in the Allt a'Mharcaidh is around 850 mm, with annual evaporation losses of around 350 mm. Hydrological flow paths in the Allt a'Mharcaidh catchment have been extensively investigated (Wheater et al, 1993;Jenkins et al, 1993;Soulsby et al, 1998Soulsby et al, , 1999Soulsby et al, , 2000 and provide a general picture of the processes likely to be important in the other catchments. The annual hydrological regime is dominated by the winter period where substantial snow pack accumulation can result in large snowmelt events in the late winter and early spring (JanuaryApril).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Mean annual run-off in the Allt a'Mharcaidh is around 850 mm, with annual evaporation losses of around 350 mm. Hydrological flow paths in the Allt a'Mharcaidh catchment have been extensively investigated (Wheater et al, 1993;Jenkins et al, 1993;Soulsby et al, 1998Soulsby et al, , 1999Soulsby et al, , 2000 and provide a general picture of the processes likely to be important in the other catchments. The annual hydrological regime is dominated by the winter period where substantial snow pack accumulation can result in large snowmelt events in the late winter and early spring (JanuaryApril).…”
Section: Study Areamentioning
confidence: 99%
“…The large areas of freely draining alpine soils appear to contribute a substantial amount of groundwater recharge. Complex groundwater flow systems in the catchments discharge at local springs in the upper slopes of the catchment or into the stream channel and riparian zones in the valley bottom (Soulsby et al, 1998. Geochemically-based hydrograph separation and semi-distributed modelling implies that 40-60% of annual run-off is sustained from (Soulsby and Dunn, 2001).…”
Section: Study Areamentioning
confidence: 99%
“…Hooper et al (1990) showed that groundwater is an important component in the Panola catchment but the heterogeneity of groundwaters made end member identification difficult. Groundwater also accounts for 50 60% of total annual runoff from an upland grantitic catchment in Scotland, (Soulsby et al, 1998).…”
mentioning
confidence: 99%
“…The occurrence of base-rich alkaline groundwater has been confirmed at Beddgelert in common with upland acidsensitive sites elsewhere in Wales and in Scotland (Soulsby et al, 1998). The presence of groundwater helps to account for fluctuations in the calcium content of stream water in response to flow and the relatively large mass flux of calcium at the catchment outflows which could not be explained by sources within the soil profile at Beddgelert (Stevens et al, 1989).…”
Section: Discussionmentioning
confidence: 80%